2010
DOI: 10.1182/blood-2009-11-252460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vascular endothelial growth factor and its receptor KDR on the transendothelial migration and local trafficking of human T cells in vitro and in vivo

Abstract: In these studies, we find that the vascular endothelial growth factor (VEGF) receptor KDR is expressed on subsets of mitogenactivated CD4 ؉ and CD8 ؉ T cells in vitro. We also found that KDR colocalizes with CD3 on mitogen-activated T cells in vitro and on infiltrates within rejecting human allografts in vivo. To evaluate whether VEGF and KDR mediate lymphocyte migration across endothelial cells (ECs), we used an in vitro live-time transmigration model and observed that both anti-VEGF and anti-KDR antibodies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 50 publications
(100 reference statements)
2
44
0
Order By: Relevance
“…[1][2][3]38 Activation responses and proinflammatory intracellular signals in ECs are initiated and coordinated by cytokines, 38 growth factors, 2,28 and cell-cell surface receptor-mediated interactions. [38][39][40] In contrast, EC-dependent signals mediating inflammation resolution are poorly defined and less well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]38 Activation responses and proinflammatory intracellular signals in ECs are initiated and coordinated by cytokines, 38 growth factors, 2,28 and cell-cell surface receptor-mediated interactions. [38][39][40] In contrast, EC-dependent signals mediating inflammation resolution are poorly defined and less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…A description of the immunofluorescence technique used in these studies is provided in supplemental Materials and methods, as previously reported. 28 …”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Ingenuity analysis of the VEGFR2 pathway showed an up-regulation of NME2 and PIM1, VEGFR2 responsive genes, suggesting that VEGFR2 was functionally active (SI Appendix). VEGFR2 is expressed on T cells constitutively at low levels (16,17); however the function of VEGFR2 in lymphocytes is not well understood. To investigate the role of VEGFR2 in Tat induced T-cell activation, T cells were treated with the VEGFR2-specific inhibitor SU1498, which dosedependently inhibited IL-17 production ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is a general consensus that VEGF is a dominant factor mediating vascular remodeling, and it is possible that its expression is a key physiological response to enable repair following acute and chronic injury [38]. However, its newly described effects on the chemotaxis and activation of effector T cells [39-41] and its potential effects on immunoregulatory T cells [42-45] have broad biological and clinical implications for the understanding of chronic rejection.…”
Section: Central Role For Vegf In the Chronic Rejection Intragraft MImentioning
confidence: 99%